Pelaksanaan Program Komunikasi Pembangunan Bidang Keluarga Berencana Strategi Komunikasi Bapermas Kota Surakarta dalam Sosialisasi Program Keluarga Berencana - WAHID, MUHAMAD ABDURROHMAN, Agus Triyono, S.Sos, M.Si, Joko Sutarso, SE., M.Si (2016)
The implementation of the family planning program, the Government of Surakarta assigned tasks to the Agency for Community Empowerment, Women's Empowerment, Child Protection and Family Planning (Bapermas, PP, PA and KB). Business implementation of the Family Planning Program require a serious also the right strategy. Controlling the rate of population growth is key to the success of which is done through an increase in the number of FP and FP independent. Baperma communication strategy, Family Planning Sector plays an important role in addressing the population growth rate, it takes hard work to realize all the strategies, family planning program is said to be a tool to prevent the growth of population. One way is to disseminate the idea to raise public awareness about the importance of family planning programs through socialization. The purpose of this study was to determine the communication strategy Bapermas Surakarta in Socialization Program Family Planning. This research uses descriptive qualitative research methods. The subject of research from various sources of information obtained for research data, in the form of informants, documents and activities. Data collection techniques of interview, observation and documentation. Analyzed using Miles and Huberman. The results of the research the acquisition of implementation of development communication strategy in disseminating family planning program has been going well, as noted in the study found their implementation has not yet reached the optimal target achievement though is successful. The socialization of family planning programs by Bapermas Surakarta do with the communication strategy of development through methods of various activities such as talk shows, public service announcements and outreach.